2022
DOI: 10.1590/fst.88421
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antioxidant activities of polysaccharide extracted from Benincasa hispida var. chieh-qua How

Abstract: The water-soluble polysaccharide (BHCP) was isolated from the hot aqueous extract of Chieh qua (Benincasa hispida var. chieh-qua How) fruit. The polysaccharide was found to contain D-galactose and D-glucose in a molar ratio of 2.59:1 with both α-and β-glycosidic bond. The strong free radicals scavenging activity on DPPH, ABTS, and hydroxyl radicals of the BHCP was demonstrated, and showing the BHCP from Chieh qua has potential application value on the functional food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The scavenging capacity of four polysaccharides (cPRP, PRP0, PRP1 and PRP2) on 2,2-difenil-1-picril-hidrazil (DPPH) and hydroxyl radicals (•OH) was evaluated according to previous methods ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The scavenging capacity of four polysaccharides (cPRP, PRP0, PRP1 and PRP2) on 2,2-difenil-1-picril-hidrazil (DPPH) and hydroxyl radicals (•OH) was evaluated according to previous methods ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study by Chen et al (2019) also showed that the DPPH free radical scavenging ability was gradually increased with a decrease in the molecular weight of fucoidan at the same concentration (Chen et al, 2019). Wang et al (2022) reported that after hot water extraction, ethanol precipitation, and deproteinization by Sevage method, the Benincasa hispida polysaccharide showed preferable scavenging ability against DPPH free radicals and the higher the dose, the better the scavenging effect (Wang et al, 2022).…”
Section: Effect Of Molecular Weight On Dpph Radical Scavenging Activitymentioning
confidence: 95%
“…DPPH and ABTS radical cation scavenging activity were measured using the method reported before 23,24 .…”
Section: Antioxidant Activitymentioning
confidence: 99%